Changes in Quality of Purse Red Carp during Deep-frying at Different Temperatures - Ziyi LIU; Yuting WANG; Qianzhu E; Yuwei LIU; Jianhua XIE; Qiang YU; Yi CHEN (Shipin gongye ke-ji)
Wuyuan purse carp, a unique dish in Jiangxi, was nutritious and delicious. The effects of temperatures (120, 140, 160, 180 ℃) and times (2, 4, 6, 8 min) on sensory quality, physicochemical properties and flavor of purse carp during frying were investigated, with changes in apparent quality (texture, color) and physicochemical properties (pH, volatile basic nitrogen (TVB-N), thiobarbituric acid value (TBARS) being analyzed, and the dynamic changes of flavor being monitored through electronic nose, electronic tongue and gas chromatography-mass spectrometry (GC-MS). The results showed that during frying, the yield of purse carp was significantly (P<0.05) reduced, meanwhile, the hardness and chewiness were enhanced, the color changed from reddish yellow to reddish brown, the TVB-N value continued to increase (4.82~11.14 mg/100 g), the pH (6.89~7.38) and TBARS value (0.14~0.59 mg MDA/kg) increased and then decreased. In terms of flavor, the results of electronic nose and tongue tests showed that the flavor of purse carp changed significantly with increasing temperature and time. After frying, the saltiness and umami taste of purse carp increased, and the types and contents of volatile compounds increased significantly. A total of 73 volatile compounds were identified, 13 key flavor compounds were screened for OAV values greater than 1. After temperature reached 160 ℃, flavor substances such as pyrazines and furans generated in the fried purse carp. When fried at 160 ℃ for 6 min, moderate hardness and a light brown surface were observed, with the TVB-N value measured at 6.77 mg/100 g and the TBARS value determined as 0.37 mg MDA/kg, indicating moderate oxidation degree. Sufficient flavor substances were demonstrated by the volatile compounds content ranking second, which suggested that frying at 160 ℃ for 6 min was more suitable. This study provides a theoretical basis for change and improvement of the quality of purse-fried carp.